Reperfusion repercussions: A review of the metabolic derangements following resuscitative endovascular balloon occlusion of the aorta. Issue 2 (August 2020) - Abid, Mustafa; Neff, Lucas P.; Russo, Rachel M.; Hoareau, Guillaume; Williams, Timothy K.; Grayson, J. Kevin; DuBose, Joseph J.; Lendrum, Robbie; Johnson, M. Austin
Abstract : BACKGROUND: Current resuscitative endovascular balloon occlusion of the aorta (REBOA) literature focuses on improving outcomes through careful patient selection, diligent catheter placement, and expeditious definitive hemorrhage control. However, the detection and treatment of post-REBOA ischemia-reperfusion injury (IRI) remains an area for potential improvement. Herein, we provide a review of the metabolic derangements that we have encountered while managing post-REBOA IRI in past swine experiments. We also provide data-driven clinical recommendations to facilitate resuscitation post-REBOA deflation that may be translatable to humans. METHODS: We retrospectively reviewed the laboratory data from 25 swine across three varying hemorrhagic shock models that were subjected to complete REBOA of either 45 minutes, 60 minutes, or 90 minutes. In each model the balloon was deflated gradually following definitive hemorrhage control. Animals were then subjected to whole blood transfusion and critical care with frequent electrolyte monitoring and treatment of derangements as necessary. RESULTS: Plasma lactate peaked and pH nadired long after balloon deflation in all swine in the 45-minute, 60-minute, and 90-minute occlusion models (onset of peak lactate, 32.9 ± 6.35 minutes, 38.8 ± 10.55 minutes, and 49.5 ± 6.5 minutes; pH nadir, 4.3 ± 0.72 minutes, 26.9 ± 12.32 minutes, and 42 ± 7.45 minutes after balloon deflation in the 45-, 60-, and 90-minute occlusion models, respectively). All models displayed persistent hypoglycemia for more than an hour following reperfusion (92.1 ± 105.5 minutes, 125 ± 114.9 minutes, and 96 ± 97.8 minutes after balloon deflation in the 45-, 60-, and 90-minute occlusion groups, respectively). Hypocalcemia and hyperkalemia occurred in all three groups, with some animals requiring treatment more than an hour after reperfusion. CONCLUSION: Metabolic derangements resulting from REBOA use are common and may worsen long after reperfusion despite resuscitation. Vigilance is required to detect and proactively manage REBOA-associated IRI. Maintaining a readily available "deflation kit" of pharmacological agents needed to treat common post-REBOA electrolyte abnormalities may facilitate management. LEVEL OF EVIDENCE: Level V.